Grammatical Classification of Chengyu: A Commentary on Adverbial Chengyu - Han, Fang (Estudios Complutenses de Asia Oriental, 2025)
In both Chinese learning materials and studies, chengyu always appears as a special element because of the cultural connotation it contains. Much focus has been placed on the explanation of its origin and semantic value. However, the difficulty lies not only in understanding its meaning, but also in its grammatical function, which has not been fully researched. In this paper, we will take adverbial chengyu as an example to discuss the classification of chengyu and its grammatical function. We will approach this topic by application of the criterion of Spanish idioms classification with adverbial chengyu in the Historical Study of Shuyu incorporating examples of the BBC corpus.